Barriers to the effective implementation of e-parliament in Africa: A case study on the 8th Nigeria National Assembly (2015-2019) - Abdullahi A.; Mustafa A.S. (Inderscience Publishers, 2023)
The level of information and communication technology (ICT) implementation in a country may have a significant effect on the successful realisation of e-parliament for a more accessible, transparent, effective and representative legislature. Thus, highlighting the importance of parliaments to embrace digital transformation and ICT for citizen engagement amid the novel COVID-19 pandemic. Despite several perceived benefits of e-parliament, some African nations, including Nigeria, are still at the initial phase of adopting this technology. This study examines barriers to e-parliament adoption and implementation in Africa with a distinct focus on the Nigerian National Assembly context. Descriptive survey research design together with stratified random sampling technique were employed for this research. A questionnaire was used as a study instrument and distributed to legislators of the Nigerian Legislature. Three hypotheses were formulated and tested with analysis of variance (ANOVA) statistical model. Our results show that, inter alia, limited ICT infrastructure, low level of ICT literacy and absence of necessary ICT regulatory framework serves as major hindrances to the successful adoption of e-parliament in Nigeria. We explore the implications of our findings and also consider future potential directions. Copyright 2021 Inderscience Enterprises Ltd.